Dampak pandemi COVID-19 terhadap peningkatan hobi berkebun - Christmastuti Nur; Stefani Natalia Sabatini (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2023)
The implementation of Community Activity Restrictions set by the government during the COVID-19 pandemic encouraged people to pursue gardening as a hobby while undergoing independent isolation or quarantine at home. The increasing selling price of ornamental plants and the emergence of various equipment products mark the guard. This study aims to determine the impact of the COVID-19 pandemic on increasing the hobby of gardening and to identify consumer preferences in purchasing gardening equipment products. The benefit of this research is to produce recommendations for gardening equipment designs that are desirable to consumers. Quantitative methods were used to describe trends in consumer behavior through online surveys of one hundred people who have a gardening hobby. Based on the analysis of the questionnaire, it is known that the COVID-19 pandemic has impacted the gardening hobby in the community. The three most essential tools in gardening are pots, watering tools, and shelves. In choosing a pot, the prominent factors considered by consumers are design, material, and price. The types of pots most respondents chose were plain earthenware pots and white plastic pots. Most respondents choose high-straight iron and wood-iron shelves or minimalist iron shelves. Regarding to pot decorations, respondents chose metal-wood pot stand, or rattan pot stand, over other decorative products such as pot hangers or fabric pot covers.